Exploring the genomes of East African Indicine cattle breeds reveals signature of selection for tropical environmental adaptation traits - Taye, M.; Wonseok Lee; Caetano-Anolles, Kelsey; Dessie, Tadelle; Seoae Cho; Sung Jong Oh; Hak-Kyo Lee; Heebal Kim (Informa UK Limited, 2018)
African indigenous cattle breeds have been reared within the continent for millennia. Due to the harsh tropical environmental conditions (e.g. sever disease and parasite prevalence, high temperatur...